Boycott, Intention, and Purchase Decisions among Generation Z: A PLS-SEM Analysis Based on Qawāʿid Fiqhiyyah - Qotrunnada; Syihabudin; Muhamad Fakhrudin; Suryani, Risa (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2025)
Abstract: Purchase or avoidance decisions regarding fast-food brands associated with pro-Israel affiliations among Generation Z university students in Banten Province are examined through two complementary lenses: PLS-SEM modeling and reasoning grounded in Qawāʿid Fiqhiyyah. The sample comprises 125 respondents, all active social-media users. Findings indicate that consumer animosity does not affect either purchase intention or purchase decision. Religiosity exerts a positive and statistically significant direct effect on purchase decisions, but not on intentions. Exposure to and participation in social-media boycott campaigns have positive and significant effects on both intention and decision, while the indirect pathway via intention is observed only from boycott to decision and is small in magnitude. Purchase intention itself significantly predicts purchase decisions, also with a small effect. Document analysis links these estimates to three legal maxims. Al-umūr bi maqāṣidihā explains value-driven execution that can bypass the intention phase, clarifying why religiosity operates at the decision point. Al-‘ādah muḥakkamah accounts for the persistence of habit, store proximity, and promotions that attenuate the move from animosity to action. Al-yaqīn lā yazūlu bi al-shakk underscores the need for credible evidence of brand affiliation so that intention and decision are not stalled by doubt. Practical implications include evidence-based value education, accessible halal substitutes, competitive pricing, and supply-chain transparency to foster yaqīn and stabilize ethical compliance in everyday choices. The study enriches Islamic Business Law with an auditable, replicable normative-empirical bridge.   Abstrak: Keputusan membeli atau menghindari merek fast food yang diasosiasikan pro-Israel pada mahasiswa Generasi Z di Provinsi Banten dibaca melalui dua lensa yang saling melengkapi, yakni pemodelan PLS-SEM dan penalaran Qawāʿid Fiqhiyyah. Sampel berjumlah 125 responden yang seluruhnya pengguna media sosial. Hasil menunjukkan consumer animosity tidak berpengaruh terhadap intensi maupun keputusan. Religiusitas berpengaruh positif dan signifikan langsung pada keputusan, namun tidak pada intensi. Paparan serta partisipasi pada gerakan boikot di media sosial berpengaruh positif dan signifikan pada intensi dan keputusan, sementara pengaruh tidak langsung yang melalui intensi hanya terbukti pada jalur boikot menuju keputusan dan berukuran kecil. Intensi sendiri berpengaruh signifikan terhadap keputusan dengan efek yang juga kecil. Analisis dokumen menautkan angka tersebut pada tiga kaidah. Al-umūr bi maqāṣidihā menjelaskan eksekusi nilai yang dapat memintas fase niat sehingga religiusitas bekerja pada titik keputusan. Al-‘ādah muḥakkamah menerangkan daya lekat kebiasaan, kedekatan gerai, dan promosi yang menetralkan dorongan menjauh sehingga animosity tidak otomatis menjadi aksi. Al-yaqīn lā yazūlu bi al-shakk menegaskan pentingnya kepastian afiliasi merek agar intensi dan keputusan tidak tertahan oleh keraguan. Implikasi praktis mengarah pada edukasi nilai yang berbasis bukti, penyediaan substitusi halal yang mudah diakses, penyesuaian harga yang kompetitif, serta transparansi rantai pasok agar yaqīn terbentuk dan kepatuhan etis lebih stabil pada level keputusan sehari-hari. Temuan ini memperkaya Hukum Bisnis Islam dengan jembatan normatif-empiris yang dapat diaudit dan direplikasi.